Short-term outcomes of transcatheter closure of secundum atrial septal defect in children and adolescents: An experience of two centers in Upper Egypt - Safaa H. Ali; Amal El Sisi; Duaa M. Raafat; Salah-Eldin Amry; Sharaf E.D. Mahamoud (Journal of the Saudi Heart Association, 2018)
Background: The aim of this study was to evaluate the acute and short-term outcomes of transcatheter closure of secundum atrial septal defect (ASD) in children and adolescents in the first 4-year experience in two institutional centers in Upper Egypt. Methods: This was a retrospective cohort study including 135 children and adolescents who underwent ASD closure between April 2012 and May 2016. A review of the acute and short-term outcomes and adverse events was performed. Results: The patients had a median age of 5 years (interquartile range: 3–9 years), 71% of patients were ≤5 years, and median weight was 17 kg (interquartile range: 13–30 kg). Single defects were observed in 113 patients (84%). The remainder had multiple or multifenestrated defects that were closed by a single device. The mean defect size of single defects and the mean interatrial septum length were 15.24 ± 5.16 mm and 38.13 ± 6.3 mm, respectively. The ratio of device to TEE (Transoesophageal echocardiography) size of ASD was 1.19 ± 0.12. The devices were implanted successfully in 98.5% of patients. Six cases had concordant PS (Pulmonary stenosis), patent ductus arteriosus or perimembranous ventricular septal defect and were treated with balloon dilation, or closure. No residual flow was seen after device placement except in one patient with multiple fenestrations. There were five high-severity adverse events (3.7%) with no mortality. Device erosion was confirmed in one of two patients with massive haemopericardium; embolization of the device with retrieval in one patient; and heart block was detected in two cases. No cardiac perforation, device erosion, embolization, thrombus formation, or clinical evidence of bacterial endocarditis was observed during follow-up. Conclusions: Transcatheter closure of ASDs in children and adolescents was feasible and safe in the first 4 years experience in our centers, with good short-term outcome. Balloon sizing is not necessary for transcatheter closure of secundum ASD. Multiple defects can be safety closed by a single device.